Environmental education in a hospital institution and PGRSS construction (Research, Society and Development, 2021)
In Brazil, few hospitals operate seriously in the management of solid waste (RS). The Health Solid Waste Management Plan (PGRSS) is an ally of health institutions, with regard to the commitment to quality and environmental protection. A qualitative case study was carried out at the Municipal Hospital of Goianinha. The objective was to analyze the management of the institution's SR, with the subject responsible for the employees responsible for cleaning, Serial Service Agents, and under their perspective to propose improvements in daily practices regarding SR management. The Environmental Education tool was used to disseminate knowledge and thus add environmental values ​​to the professionals involved. As a result, the need for Environmental Education was continuously observed with employees and the implementation of a Health Solid Waste Management Plan at the location, which was prepared and offered to the institution involved.